Halal tourism: definition, justification, and scopes towards sustainable development - Azam, Md. Siddique E.; Abdullah, Moha Asri; Abdul Razak, Dzuljastri (Zes Rokman Resources, 2019)
Sustainability is a worldwide concern embedded in every sphere of human life including economic, environmental, and as well as social aspects. Similarly, tourism is one of the major areas of many economies where sustainability is a rising concern. Sustainable tourism has been defined by several organizations like WTO, ICOMOS, and many studies as well. Additionally, Halal tourism, often termed as Islamic tourism or Muslim friendly tourism, is a new concept in the tourism industry that opens up new and exciting opportunities for enhancing economic growth. The idea 'Halal' additionally relates the idea 'Toyyib' which means great. Along these lines, the importance of 'Halal' is anything which is allowed by sharia’h and great for human being. The coordination of moral qualities alongside religious qualities opens up the limit of halal tourism from 2.8 billion Muslim consumers to non-Muslim consumers too around the globe. The fusion of halaln-toyyiban (Lawful and goodness) can be related to every field of sustainability. Halal tourism, one of the components of the Halal industry, in fact, addresses a few of the seventeen sustainable development goals (SDGs) and can have a significant contribution towards sustainability. It has now become a lifestyle choice of Muslim travelers and also drawing the attention of non-Muslims as well. Recent data shows Muslim spending on Halal travel was USD169 billion in 2016 and estimated to reach USD283 billion by 2022. It is essential to understand and also spread the sustainable aspect of Halal tourism in the global economy which can enhance the growth of the industry. This perspective will also make all consumers welcome and accept halal tourism keeping aside any religious zeal. Based on literature review and secondary data, this paper defines and justifies the term ‘Halal’ accepted and welcomed by all. The study provides the definition of Halal in the form of a table where the term has been adopted as an acronym. Each letter of the acronym HALAL stands for different attributes of Halal concept. Combining all these aspects together completes the definition of Halal. The definition of Halal tourism has also been deducted integrating all the aspects (Shariah law, target customer, destination, purpose, and product and services) together to be covered in terms of both sustainable and halal tourism. Simultaneously, it justifies the definitions of tourism from both sustainable and Islamic perspective. The study also identifies how halal tourism addresses four important SDGs and contributes towards sustainable development. Additionally, and it explores the scope of halal tourism to contribute more in relation to other SDGs in a greater extent. This paper contributes to the halal industry, that represents Islamic economy as well, providing a universal definition of Halal, clarifying the sustainability perspective of both Halal and halal tourism, and identifying the SDGs addressed by Halal tourism. This study opens up greater research scopes regarding other components of Halal industry and sustainable development.